'Team capital' in quality improvement teams: findings from an ethnographic study of front-line quality improvement in the NHS. Issue 2 (26th May 2020) - Montgomery, Catherine; Parkin, Stephen; Chisholm, Alison; Locock, Louise
Abstract : Background: Teamwork is important in the design and delivery of initiatives in complex healthcare systems but the specifics of quality improvement (QI) teams are not well studied. Objective: To explain the functioning of front-line healthcare teams working on patient-centred QI using Bourdieu's sociological construct of capital. Methods: One medical ward from each of six NHS Trusts in England participated in the study, purposively selected for a range of performance levels on patient experience metrics. Three ethnographers conducted focused ethnography for 1 year, using interviews and observations to explore the organisation, management and delivery of patient-centred QI projects by the six front-line teams. Data were analysed using Bourdieu's typology of the four forms of capital: economic, social, symbolic and cultural. Results: While all teams implemented some QI activities to improve patient experience, progress was greater where teams included staff from a broad range of disciplines and levels of seniority. Teams containing both clinical and non-clinical staff, including staff on lower grades such as healthcare assistants and clerks, engaged more confidently with patient experience data than unidisciplinary teams, and implemented a more ambitious set of projects. We explain these findings in terms of 'team capital'. Conclusion: Teams that chose to restrict membership to particular disciplines appeared to limit their capital, whereas more varied teams were able to draw on multiple resources, skills, networks and alliances to overcome challenges. Staff of varying levels of seniority also shared and valued a broader range of insights into patient experience, including informal knowledge from daily practice. The construct of 'team capital' has the potential to enrich understanding of the mechanism of teamwork in QI work.